Smurf soup - Peyo; Delporte, Y. (New York : Papercutz Printing, 2012)
Challenged by Gargamel to make the world's most delicious soup or face ingestion by a hungry giant, the Smurfs scramble to distract the insatiable giant while Papa Smurf concocts a potion that will turn the giant against Gargamel.
Primary
700-799
Keywords: Smurfs (Fictitious characters) -- Comic books, strips, etc. -- Juvenile literature; Caricatures and cartoons; Fantasy; France; Graphic novels